The Georeferencing of Old Cartography in Geographic Information Systems (GIS): Review, Analysis and Comparative Study of Georeferencing Software - Cascón-Katchadourian, Jesús; Alberich-Pascual, Jordi (Revista General de Información y Documentación, 2021)
Contemporary organizations have faced the growing management of cartographic documentation, some of them of heritage interest. There are numerous institutions that are digitizing, georeferencing and publishing their historical cartography. The motivation of this research is to facilitate the choice of the most appropriate software to perform these tasks. This article carries out the critical review and analysis of four Geographic Information Systems (GIS) of full significance today. After systematizing the general characteristics and modules that must satisfy this type of application, we proceed to the detailed evaluation of the selected Geographic Information Systems, reaching as a result the discussion of the advantages that each one of them provides, of their distinctive characteristics, as well as their professional adequacy.